An Analysis of The Offense of Unpleasant Action in Article 335 Paragraph (1) of The Indonesian Criminal Code - Xavier Nugraha; Kusuma Wardani Raharjo; Ahmad Ardhiansyah; Alip Pamungkas Raharjo (Jurnal Hukum Volkgeist, 2021)
The Constitutional Court as the guardian of the constitution and the guardian of human rights has the duty to ensure that the Law does not contradict the constitution and does not violate human rights. One of the manifestations of this can be seen in the Constitutional Court Decision Number 1 / PUU-X / 2013, where the Constitutional Court removed the element "Some other deeds or unpleasant treatment/act" in Article 335 paragraph (1) of the Criminal Code. With the removal of the core elements of Article 335 paragraph (1) of the Criminal Code, raises questions related to the existence of the offense whether it still exists or not. Based on this, this study will examine 1) Application of Article 335 of the Criminal Code Before the Decision of the Constitutional Court Number 1 / PUU-X / 2013 and 2.) Application of Article 335 of the Criminal Code After the Decision of the Constitutional Court Number 1 / PUU-X / 2013. This research is a normative legal research with a statute approach, conceptual approach, and case approach. Based on this research, it was found that after the Constitutional Court Decision Number 1 / PUU-X / 2013 that offenses of unpleasant acts had been reconstructed into forced offenses.